Acaricidal Toxicities of 1-Hydroxynaphthalene from Scutellaria barbata and Its Derivatives against House Dust and Storage Mites - Yang, Ji-Yeon; Kim, Min-Gi; Lee, Hoi-Seon (Planta Medica, 2013)
The essential oil of Scutellaria barbata was extracted using a steam distillation and then evaluated via fumigant and contact toxicity bioassays against Dermatophagoides farinae, Dermatophagoides pteronyssinus, and Tyrophagus putrescentiae. The acaricidal toxicities of 1-hydroxynaphthalene from S. barbata oil and its derivatives were determined and compared with those of benzyl benzoate. Based on the LD50 values of 1-hydroxynaphthalene derivatives against D. farinae, D. pteronyssinus, and T. putrescentiae, obtained using a fumigant toxicity bioassay, the acaricidal activity of 1-hydroxynaphthalene (2.11, 2.37, and 4.50 µg/cm2) was 4.76, 6.00, and 2.68 times higher than that of benzyl benzoate (10.05, 9.50, and 12.50 µg/cm2) in the corresponding order, which was followed by that of 2-hydroxynaphthalene (9.50, 9.00, and 11.50 µg/cm2). On the contact toxicity bioassay, the acaricidal activity of 1-hydroxynaphthalene (0.79, 0.92, and 2.50 µg/cm2) was 9.49, 6.52, and 3.76 times higher than that of benzyl benzoate (7.50, 6.00, and 9.41 µg/cm2), which was followed by that of 2-hydroxynaphthalene (4.21, 4.80, and 6.50 µg/cm2). In conclusion, our results indicate that S. barbata oil and 1-hydroxynaphthalene derivatives might be effective natural agents for the management of house dust and storage mites.
Keywords: Dermatophagoides farina; Dermatophagoides pteronyssinus; 1-hydroxynaphthalene; Lamiaceae; Scutellaria barbata; Tyrophagus putrescentiae